Sistem Pengolahan Buku Tamu Berbasis Web Pada PTPN4 Menggunakan Metode Waterfall - Dea Syahfira Hasibuan; Mazayah Tsaqofah; Sriani Sriani (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The implementation of a web-based guest book at PTPN4 aims to enhance visitor management and improve operational efficiency. This system allows for real-time data entry and retrieval, enabling staff to monitor visitor information effectively. By transitioning from a traditional paper-based guest book to a digital solution, PTPN4 seeks to minimize administrative burdens, reduce errors, and streamline the check-in process. Furthermore, the web-based system facilitates better data analysis, helping management make informed decisions about visitor engagement and security protocols. Overall, this initiative is expected to contribute to a more organized and efficient operational environment at PTPN4